2018
DOI: 10.18632/oncotarget.24023
|View full text |Cite
|
Sign up to set email alerts
|

ZB716, a steroidal selective estrogen receptor degrader (SERD), is orally efficacious in blocking tumor growth in mouse xenograft models

Abstract: Advances in oral SERDs development so far have been confined to nonsteroidal molecules such as those containing a cinnamic acid moiety, which are in earlystage clinical evaluation. ZB716 was previously reported as an orally bioavailable SERD structurally analogous to fulvestrant. In this study, we examined the binding details of ZB716 to the estrogen receptor alpha (ERα) by computer modeling to reveal its interactions with the ligand binding domain as a steroidal molecule. We also found that ZB716 modulates ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…A glide tool (Friesner et al, 2006) was used for docking of the fulvestrant. Since the structures of fulvestrant and ZB716 are similar, the same protocol using a flexible docking simulation was performed with the Induced Fit protocol (IFD) method as previously reported (Guo et al, 2018). The docking complexes were refined with the protein-ligand interaction refinement tool in the Schrödinger suite.…”
Section: Comparative Modeling Quality Assessment and Model Refinementmentioning
confidence: 99%
“…A glide tool (Friesner et al, 2006) was used for docking of the fulvestrant. Since the structures of fulvestrant and ZB716 are similar, the same protocol using a flexible docking simulation was performed with the Induced Fit protocol (IFD) method as previously reported (Guo et al, 2018). The docking complexes were refined with the protein-ligand interaction refinement tool in the Schrödinger suite.…”
Section: Comparative Modeling Quality Assessment and Model Refinementmentioning
confidence: 99%
“…In both tamoxifen naive and tamoxifen resistant breast cancer cells, ZB716 potently inhibits cell proliferation and effectively degrades the hormone receptor in a dose-dependent manner. In mice, we have shown that ZB716 has far superior oral bioavailability when compared to fulvestrant [ 27 28 ], and in two breast cancer xenograft models including a patient derived xenograft (PDX) model, ZB716 has proven to be a more efficacious SERD than fulvestrant in inhibiting tumor growth [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The only structural difference between ZB716 and fulvestrant is that the 3-hydroxyl group of fulvestrant is replaced by a boronic acid moiety in ZB716 [ 27 ]. The single substitution of -OH with –B(OH) 2 (Figure 1 ) is apparently responsible for the vastly improved oral bioavailability while retaining potent biological activities of ZB716 as compared to fulvestrant [ 27 28 ]. In mice and rats, oral administration of ZB716 at 10 mg/kg afforded peak plasma concentrations in excess of 100 ng/mL, a level significantly higher than the 20 ng/mL observed for fulvestrant administered at similar dosage via s.c. injection in animals [ 27 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations